1994
DOI: 10.1007/bf01271568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D-cycloserine and (+)-HA-966 on the locomotor stimulation induced by NMDA antagonists and clonidine in monoamine-depleted mice

Abstract: We have previously observed that an N-methyl-D-aspartate (NMDA) antagonist in combination with the alpha 2-adrenoceptor agonist clonidine produces a marked locomotor stimulation in monoamine-depleted mice. In this paper we report on how the partial glycine agonists D-cycloserine (high intrinsic activity) and (+)-HA-966 [(+)-3-amino-1-hydroxypyrrolid-2-one; low intrinsic activity] affect this response; the interaction with both an uncompetitive and a competitive NMDA antagonist was investigated. (+)-HA-966 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, in animals, compelling evidence about the involvement of NMDA receptors in the regulation of these sensory gating paradigms is currently available. In rats, disruption of sensory gating can be consistently elicited using the non-competitive NMDA antagonists PCP and MK-801, manifested in a disruption of the P50 (Adler et al 1986) and of the PPI (Mansbach and Geyer 1989;Mansbach 1991;Carlsson et al 1994;Varty and Higgins 1995;Wedzony et al 1994;Reijmers et al 1995), although competitive NMDA antagonists give rise to conßicting results (Mansbach 1991;Wedzony et al 1994;Furuya and Ogura 1997). Interestingly, PPI deÞcits induced by 7-chloro-kynurenate, a competitive antagonists of the glycine recognition site of the NMDA receptor, can be antagonized by the partial NMDA agonist D-cycloserine (Kretschmer and Koch 1997), which also has been reported to have some beneÞcial e¤ect in patients su¤ering from schizophrenia (Go¤ et al 1995;van Berckel et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, in animals, compelling evidence about the involvement of NMDA receptors in the regulation of these sensory gating paradigms is currently available. In rats, disruption of sensory gating can be consistently elicited using the non-competitive NMDA antagonists PCP and MK-801, manifested in a disruption of the P50 (Adler et al 1986) and of the PPI (Mansbach and Geyer 1989;Mansbach 1991;Carlsson et al 1994;Varty and Higgins 1995;Wedzony et al 1994;Reijmers et al 1995), although competitive NMDA antagonists give rise to conßicting results (Mansbach 1991;Wedzony et al 1994;Furuya and Ogura 1997). Interestingly, PPI deÞcits induced by 7-chloro-kynurenate, a competitive antagonists of the glycine recognition site of the NMDA receptor, can be antagonized by the partial NMDA agonist D-cycloserine (Kretschmer and Koch 1997), which also has been reported to have some beneÞcial e¤ect in patients su¤ering from schizophrenia (Go¤ et al 1995;van Berckel et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…activation. However, a number of studies have shown that systemically administered glycine site antagonists either have no effect or suppress spontaneous locomotion (Carlsson et al, 1994;Witkin, 1993;Bristow et al, 1993Bristow et al, , 1996.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, DCS might be able to antagonize the effect of elevated dopamine levels seen in schizophrenic patients through the stimulation of the NMDA receptor complex. However, DCS elicited little response when it was utilized in a mouse hyperactivity model of psychosis (115). Furthermore, in a clinical trial of seven patients with chronic schizophrenia who received 250 mg of DCS as an adjuvant to conventional neuroleptics, only one patient exhibited a slight improvement (77).…”
Section: The Use Of D-cycloserine In Aging and Cognitive Disordersmentioning
confidence: 99%